Development of high‐efficiency and low‐cost solar cells for PV‐powered vehicles application. (21st September 2020) - Yamaguchi, Masafumi; Masuda, Taizo; Araki, Kenji; Sato, Daisuke; Lee, Kan‐Hua; Kojima, Nobuaki; Takamoto, Tatsuya; Okumura, Kenichi; Satou, Akinori; Yamada, Kazumi; Nakado, Takashi; Zushi, Yusuke; et al.
Abstract: Development of high‐efficiency solar cell modules and new application fields are significant for the further development of photovoltaics (PVs) and the creation of new clean energy infrastructure based on PV. Notably, the development of PV‐powered vehicle applications is desirable and very important for this end. According to the NEDO's Interim Report "PV‐Powered Vehicle Strategy Committee, " a new broader PV markets with more than 10 GW and 50 GW in 2030 and 2040, respectively, are expected to be established when PV‐powered vehicles are developed. Cumulative PV capacity for PV‐powered vehicles will be 50 GW and 0.4 TW in 2030 and 2040, respectively. This paper presents impacts on efficiency and cost for PV‐powered vehicles. According to our survey, the use of more than 30% of high‐efficiency PV enables 30 km per day driving without external charging and the society that the majority of the family cars run by the sunlight and without supplying gas. Thus, we are developing high‐efficiency and low‐cost solar cells and modules for automobile applications. In this paper, our analytical results for the efficiency potential of various solar cells for choosing candidates of high‐efficiency solar cell modules for automobile applications. This paper also presents our recent approaches: demonstration car (Toyota Prius PHV) by using Sharp's high‐efficiency III‐V triple‐junction solar cell modules with an output power of 860 W, static low concentrator InGaP/GaAs/InGaAs triple‐junction solar cell module with efficiency of 32.84%, and so forth. Abstract : Highly efficient PV module with more than 30% equipped on family car enables 30 km per day driving. Analyses for the efficiency potential of various solar cells for high‐efficiency modules for automotive applications showed that the III‐V compound based multijunction cells and III‐V/Si tandem cells are a promising one. A test car (Toyota Prius PHV) equipped with a rated output power of 860 W PV and a static low‐concentration module with InGaP/GaAs/InGaAs triple‐junction (3‐junction or 3‐J) solar cell with 32.84% efficiency are demonstrated.